StarPEG/heparin-hydrogel based in vivo engineering of stable bizonal cartilage with a calcified bottom layer - Kunisch, Elke; Deubel, Anne-Kathrin; Hesse, Eliane; Bothe, Friederike; Diederichs, Solvig; Richter, Wiltrud (Biofabrication, 2019)
Repaired cartilage tissue lacks the typical zonal structure of healthy native cartilage needed for appropriate function. Current grafts for treatment of full thickness cartilage defects focus primarily on a nonzonal design and this may be a reason why inferior nonzonal regeneration tissue developed in vivo. No biomaterial-based solutions have been developed so far to induce a proper zonal architecture into a non-mineralized and a calcified cartilage layer. The objective was to grow bizonal cartilage with a calcified cartilage bottom zone wherein main tissue development is occurring in vivo. We hypothesized that starPEG/heparin-hydrogel owing to the glycosaminoglycan heparin contained as a building-block would prevent mineralization of the upper cartilage zone and be beneficial in inhibiting long-term progression of calcified cartilage into bone. MSCs were pre-cultured as self-assembling non-mineralized cell discs before a chondrocyte-seeded fibrin- or starPEG/heparin-hydrogel layer was cast on top directly before ectopic implantation. Bizonal cartilage with a calcified bottom-layer developed in vivo showing stronger mineralization compared to in vitro samples, but the hydrogel strongly determined outcome. Zonal fibrin-constructs lost volume and allowed non-organized expansion of collagen type X, ALP-activity and mineralization from the bottom-layer into upper regions, whereas zonal starPEG/heparin-constructs were of stable architecture. While non-zonal MSCs-derived discs formed bone over 12 weeks, the starPEG/heparin-chondrocyte layer prevented further progression of calcified cartilage into bone tissue. Conclusively, starPEG/heparin-hydrogel-controlled and cell-type mediated spatiotemporal regulation allowed in vivo growth of bizonal cartilage with a stable calcified cartilage layer. Altogether our work is an important milestone encouraging direct in vivo growth of organized cartilage after biofabrication.
Published 30 October 2018
Gesehen am 31.07.2019